On-Demand Release of Anti-Infective Silver from a Novel Implant Coating Using High-Energy Focused Shock Waves - Jan Puetzler; Julian Hasselmann; Melanie Nonhoff; Manfred Fobker; Silke Niemann; Christoph Theil; Georg Gosheger; Martin Schulze (MDPI AG, 2023)
Implant-related infections are a significant concern in orthopedic surgery. A novel anti-infective implant coating made of bioresorbable polymer with silver nitrate was developed. A controlled release of silver ions into the vicinity of the prosthesis can be triggered on-demand by extracorporeal shock waves to effectively combat all clinically relevant microorganisms. Microscopy techniques were used to examine the effects of shock wave application on coated titanium discs. Cytotoxicity was measured using a fibroblast proliferation assay. The anti-infective effect was assessed by monitoring the growth curves of three bacterial strains and by conventional culture. Microscopic analysis confirmed surface disruption of the coatings, with a complete release of silver in the focus area after shock wave application. Spectrometry detected an increase in silver concentration in the surrounding of the discs that surpassed the minimum inhibitory concentration (MIC) for both S. epidermidis RP62A and E. coli ATCC 25922. The released silver demonstrated an anti-infective effect, significantly inhibiting bacterial growth, especially at 6% and 8% silver concentrations. Cytotoxicity testing showed decreasing fibroblast viability with increasing silver concentration in the coating, with 6% silver maintaining viability above 25%. Compared to a commonly used electroplated silver coating on the market, the new coating demonstrated superior antimicrobial efficacy and lower cytotoxicity.